Evaluation of onion as a functional ingredient in the prevention of metabolic impairments associated to diet-induced hypercholesterolaemia using a multiplatform approach based on LC-MS, CE-MS and GC-MS. (December 2015) - González-Peña, Diana; Dudzik, Danuta; Colina-Coca, Clara; de Ancos, Begoña; García, Antonia; Barbas, Coral; Sánchez-Moreno, Concepción
Highlights: Onion as a functional ingredient in relation to Wistar rats metabolome was investigated. The metabolomic approach integrated results from LC-MS, CE-MS and GC-MS methodologies. S -methyl-L-cysteine and S -methylcysteine sulphoxide were identified in the HCO-fed rats. Onion supplementation modulated the effects of diet-induced hypercholesterolaemia. Mechanism involved methylation cycle, arginine and tryptophan pathways, among others. Abstract: The preventive and modulating effects of onion in metabolites affected by a high-cholesterol diet and related to molecular pathway dysfunction were examined. Plasma obtained from 24 male Wistar rats after seven weeks of experimental feeding was analysed through a non-targeted multiplatform metabolomics approach based on LC-MS, CE-MS and GC-MS methods. A cross-comparison of the three metabolic profiles [I) control (C) group, II) high-cholesterol (HC) group and III) high-cholesterol enriched with onion (HCO) group] pointed out two sulphur metabolites, S -methyl-L-cysteine and S -methylcysteine sulphoxide, as markers of onion intake and evidenced the possibilities to regulate key metabolites. Thus, the methylation cycle, arginine and tryptophan pathways, the modulation of 3-methylhistidine, as well as the routes involved in the glycerophospholipids transformation have been highlighted. This study suggests that onion's biologically active compounds take a prominent role in ameliorating hypercholesterolaemia and related complications through the regulation of altered metabolic pathways.